(untitled) (IIUC Business Review, 2022)
The purpose of this paper is to develop the features as well as framework of employee performance management from Islamic point of view. This is a conceptual paper written using secondary materials available in Qur’an, sunnah, and other published literature. The paper has developed both the features as well as framework to manage the performance of employee from Islamic perspective. The paper has some implications for managers and employees who would like manage performance from Islamic perspective in Muslim countries representing one fourth of the world population. While many studies, partially, have focused on traditional performance management sparing the demand of Muslim world, in this paper, the author opens a new avenue contributing to the literature on performance management from Islamic perspective. The proposed framework will be of genuine interest and benefits to Islamic as well as non-Islamic employers, managers, employees, academicians, and policy makers because Islam as a religion of nature can solve problems of all. IIUC Business Review Vol. 9, Dec. 2020 pp. 47-76